Women, Business and the Law 2012 : Removing Barriers to Economic Inclusion - World Bank (World Bank, Washington, DC, 2017)
Women, business and the law focuses on this critical piece of the puzzle, objectively highlighting differentiations on the basis of gender in 141 economies around the world, covering six areas: accessing institutions, using property, getting a job, providing incentives to work, building credit and going to court. Women, business and the law describes regional trends and shows how economies are changing across these six areas, tracking governments' actions to expand economic opportunities for women. For men and women throughout the developing world, the chance to start and run a business or get a good job is the surest hope for a way out of poverty. It also requires good business regulation, suited to the purpose, streamlined and accessible, so that the opportunity to build a business or have a good job is dependent not on connections, wealth or power, but on an individual's initiative and ability. The doing business report has led the way in providing data to countries about creating a sounder and more streamlined business environment. Women, Business, and the Law 2012 are the second in this series of reports. This edition retains the same basic structure of the 2010 pilot edition, while significantly expanding the depth of data covered. While the number of topics covered is the same, there has been a significant expansion of the data collected within these topics, thus addressing some of the initial shortcomings of the pilot edition. The number of economies covered has also been expanded from 128 to 141.